2005
DOI: 10.1021/jo050977s
|View full text |Cite
|
Sign up to set email alerts
|

A Noncarbohydrate Based Approach to Polyhydroxylated Pyrrolidizines:  Total Syntheses of the Natural Products Hyacinthacine A1 and 1-Epiaustraline

Abstract: [reaction: see text] A flexible route to polyhydroxylated pyrrolizidine alkaloids is described, starting from commercially available N-Boc pyrrole and using a partial reduction as the key step. Tactics for varying the stereochemistry around the ring by choice of partial reduction conditions are discussed and methods for constructing the bicyclic ring system of the pyrrolizidine targets are examined. Intramolecular S(N)2 type displacement reactions were found to be an efficient way of forming the requisite bicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…7 The synthesis of epimers 8 and a racemic synthesis have also been reported. 9 A recent study has revealed that the proposed structure of hyacinthacine C 3 is incorrect.…”
mentioning
confidence: 99%
“…7 The synthesis of epimers 8 and a racemic synthesis have also been reported. 9 A recent study has revealed that the proposed structure of hyacinthacine C 3 is incorrect.…”
mentioning
confidence: 99%
“…It has recently been reported that MsCl (MsCl = mesyl chloride) also effects this cyclization in other similar systems, with the reaction proceeding by a selective mesylation of the primary hydroxy group followed by ring closure. [4] However, treatment of 16 with MsCl at 0 8C only gave a complex mixture of products, perhaps indicating that, for the present case, the mesylation suffers from poor chemoselectively. Instead, the cyclization could be accomplished by converting the primary hydroxy moiety in 16 into the corresponding alkylbromide followed by cyclization to afford the pyrrolizidine 17 in good yields.…”
Section: Resultsmentioning
confidence: 70%
“…The combined organic phases were successively washed with an aqueous solution of NaHCO 3 (5 % w/w, 10 mL) and brine (10 mL) and dried over MgSO 4 . Filtration and evaporation of the solvents yielded a white solid (400 mg, 99 %), which was used in the following allylation without further purification.…”
Section: (2s3r4r5r)-3-hydroxy-4-[dimethyla C H T U N G T R E N N Umentioning
confidence: 99%
See 2 more Smart Citations